DICOM structured report document type definition. - Noumeir, R. (IEEE Transactions on information technology in biomedicine)
The digital imaging and communications in medicine (DICOM) standard recently introduced rules for the encoding, transmission and storage of the structured diagnostic report. This medical document can be stored and communicated with the images. It has a structure and may contain text, with links to other data such as images, waveforms and spatial or temporal coordinates. The prompt availability of the radiology report is crucial for implementing a patient electronic record. Using the extensible markup language (XML) to encode the radiology report broadens its accessibly. This paper presents a document type definition (DTD) that accurately models the DICOM structured report content, structure, and constraints.